255 Tricuspid regurgitation in the community by routine echocardiography. (8th December 2021) - Leonardi, Denis; Siviero, Valentina; Setti, Martina; Maffeis, Caterina; Fanti, Diego; Springhetti, Paolo; Cicoira, Mariantonietta; Rossi, Andrea; Ribichini, Flavio; Benfari, Giovanni
Abstract: Aims: Tricuspid Regurgitation (TR) is quite frequent in the community and often overlooked in routine clinical practice. This study aims to convey the TR rate of diagnosis and impact on survival in a geographically defined population of an Italian referral centre, considering five different clinical contexts. Methods: The study included consecutive outpatients with comprehensive echocardiography and complete clinical evaluation over 7 years of practice. Outpatients with TR greater than moderate were included, and the different clinical contexts evaluated: patients with concomitant significant mitral regurgitation (MR-TR), heart failure (HF-TR), previous open-heart surgery (postop-TR), pulmonary hypertension (PHTN-TR) and isolated TR (isolated-TR). Results: Among all consecutive echocardiograms performed in routine practice ( N =6797) in a geographically defined community, moderate or severe TR was found in 4.8% ( N = 327; mean age 76±10, 56% female). Median follow-up was 6.1 [2.2–8.9] years. TR severity was an independent determinant of survival: risk ratio for mortality of severe TR vs. moderate was 1.72 [95% CI 1.06–2.77; P = 0.03] univariate and 1.76 [95% CI 1.02–3.01; P = 0.04] after adjusted for age, sex, MR, PHTN and EF. Only 2.8% of patients underwent tricuspid valve surgery during follow-up. Outpatients with MR-TR or HF-TR held the worst prognosis (Figure). As compared to isolated-TR, the mortality risk was 2.67 [95% CI 1.05–6.78; P = 0.04] for HF-TR and 2.04 [95% CI 1.00–4.14; P = 0.05] for MR-TR. Risk ratios for mortality vs. postop-TR were 3.66 [95% CI 1.19–11.26; P = 0.02] for HF-TR and 2.79 [95% CI 1.08–7.21; P = 0.03] for MR-TR. There was no interaction between the TR clinical context and the survival impact of TR ( P =0.09). Conclusions: Significant TR is frequent in our community, comparable to key epidemiological studies. TR severity independently impacts survival in all clinical settings, and it is associated with an absolute high event-rate when present with concomitant MR or HF. These results give importance to early diagnosis with grading to be performed through accurate echocardiography and renew the interest in new and safe, less invasive percutaneous intervention to improve patients' survival.